Granica życia i śmierci. Motyw krystalicznej tafli w opowiadaniu E.T.A. Hoffmanna Kopalnie w Falun - Szybisty, Tomasz (Załącznik Kulturoznawczy, 2019)
The article seeks to analyse the symbolic significance of the crystalline membrane featured in Elis Fröbom’s dream; he is the main character of E.T.A. Hoffmann’s short story entitled The Mines of Falun. There prevails extensive consensus in the critical literature, that the dreamy landscape of the cave externalises the deepest layers of Elis’ psyche; in addition, this scene presents a key to the understanding of the whole story. The application of hermeneutical close reading and the augmentation of this analysis through invoking the vintage symbolic that accreted around the notion and image of crystal in the literature, philosophy and the science of the Romanticism era warrant the postulation of a thesis, that the mute queen appearing in the aforementioned intriguing vision can be construed as a corporeal symbolisation of death, deeply yearned for by the main character. As far as the crystalline membrane partitioning the cave into two realms is concerned, we may hazard a surmise that it functions as a peculiar delineation of life, the frontier where the inorganic world transitions into its organic extension.